Case report: A highly active refractory myasthenia gravis with treatment of telitacicept combined with efgartigimod - Chaoyue Zhang; Yangtao Lin; Qianjin Kuang; Hongjin Li; Qilong Jiang; Xiaojun Yang (Frontiers in Immunology, 2024)
There is always a lack of effective treatment for highly active refractory generalized myasthenia gravis (GMG). Recently, telitacicept combined with efgartigimod significantly reduces circulating B cells, plasma cells, and immunoglobulin G, which brings promising therapeutic strategies. We report a case of a 37-year-old female patient with refractory GMG, whose condition got significant improvement and control with this latest treatment after multiple unsuccessful therapies of immunosuppressants. The new combination deserves further attention in the therapeutic application of myasthenia gravis.